Mapping the Use of Public Accounting Firm Service by Public Companies in Indonesia - Winna Daniella Kadiman; Oktavia Oktavia; Febriani Cristina Susianti Magdalena (Budapest International Research and Critics University, 2022)
The study aims at identifying how the Covid-19 pandemics has influenced the use of Big Four and Non-Big Four Public Accounting Firm service by the public companies in Indonesia. In addition, the study also aims at identifying how the use of auditor service has been distributed among the public companies before and after the Covid-19 pandemics. This study uses data tabulation method for data analysis. This study also uses all public companies’ data that have been listed on the Indonesian Stock Exchange. The results of the study show that: (1) The companies mostly use the service of Non-Big Four Public Accounting Firm rather than that of Big Four Public Accounting Firm; (2) The number of companies audited by the Non-Big Four Public Accounting Firm has increased from 2019 until 2020, whereas the number of companies audited by the Big Four Public Accounting Firm has decreased within the same period of time; (3) Purwantono, Sungkoro & Surja is Public Accounting Firm that has the most clients (107 public companies in 2019 and 101 companies in 2020); (4) Kosasih, Nurdiyaman, Mulyadi, Tjahjo & Partners is Public Accounting Firm that has earned the second place in terms of clients (61 public companies in 2019 and 63 public companies in 2020).